2020
DOI: 10.1002/pc.25757
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multi‐walled carbon nano‐tube on mechanical behavior of glass laminate aluminum reinforced epoxy composites

Abstract: This research work is focused on development of epoxy based fiber metal laminate (FML) that comprised of multi-walled carbon nano-tube (MWCNT), glass fiber, and aluminum metal sheet. The hand layup technique was employed to fabricate the sandwich FML with different weight percentages (3, 4, and 5 wt%.) of MWCNT. The mechanical properties of the developed FMLs were determined through tensile, flexural, lap shear, and hardness tests following ASTM and IS standards. The scanning electron microscope (SEM) was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 34 publications
0
21
1
Order By: Relevance
“…Few spots of fiber pullout were noted in the core layer of FML as shown in Figure 10(F), which might have reduced the transfer of load and resulted in the decrement of UTS. The UTS, YS, elongation and strength coefficient (K) of the FML with nanoclay were noted to be greater than the FML with MWCNT [24] and LDH [25] reported in previous studies.…”
Section: Tensile Properties Of Fmlscontrasting
confidence: 67%
See 3 more Smart Citations
“…Few spots of fiber pullout were noted in the core layer of FML as shown in Figure 10(F), which might have reduced the transfer of load and resulted in the decrement of UTS. The UTS, YS, elongation and strength coefficient (K) of the FML with nanoclay were noted to be greater than the FML with MWCNT [24] and LDH [25] reported in previous studies.…”
Section: Tensile Properties Of Fmlscontrasting
confidence: 67%
“…Figure 11 showed that the FML with 3 wt% of nanoclay offered higher resistance to the flexural load. The FML with 3 and 4 wt% of nanoclay exhibited superior flexural resistance than the FML with MWCNT [24] and LDH. [25] The flexural strength (σ fl ), flexural modulus (E fl ) and flexural stiffness (K fl ) of the composites were calculated using the following equations [22] :…”
Section: Flexural Properties Of Fmlsmentioning
confidence: 93%
See 2 more Smart Citations
“…19 The effect of using nanofillermodified matrix in manufacturing of FMLs has been investigated by many researchers. [19][20][21][22][23][24][25][26][27] Megahed et al 20 studied the mechanical properties of GLARE by adding several types of nanofillers such as aluminum (Al), copper (Cu), titanium oxide (TiO 2 ), silica (SiO 2 ), aluminum oxide (Al 2 O 3 ), and nano clay (NC). They reported that adding SiO 2 nanoparticles into the composite laminates of GLARE caused a maximum improvement of 39%, 33.2%, and 108.4% in tensile strength, modulus, and toughness respectively, as compared to the unreinforced GLARE.…”
Section: Introductionmentioning
confidence: 99%